EXPERIMENTAL INVESTIGATION OF HYBRID EPOXY COMPOSITES WITH COCONUT FIBER, BAMBOO FIBER & PLASTIC PARTICULATES (International Journal of Food and Nutritional Sciences, 2021)
Plastic is one of the most common used materials in the world today, but, they causes serious environmental pollution and exhaustion of landfill space. The recycling of waste plastic recovers the material, which can be used to make new plastic products such as containers, plastic lumbers and particle boards. For this to happen, the waste plastic will first be shred into small bits making it ready for transportation and further processing. The huge quantities of these plastic categories currently being marketed will ultimately find their way to the waste dump sites. This is creating waste products problems due to its high amount of waste generated, non-bio degradability and the fastest depletion of natural resources regarding its short life cycle, therefore increased amount of material utilized in its production and waste generated.We are making this project model for recycling of plastic wastage in domestic area, industries etc. in this area the plastic waste is present in large quantity. Plastic recycling or reprocessing is usually referred to as the process by which plastic waste materials that would otherwise become solid waste are collected, separated, processed and returned to use. Waste plastic shredder is a machine that reduces used plastic bottles to smaller particles sizes to enhance its portability, easiness and readiness for use in to another new product. We can conclude that plastic is shredder with the help of plastic shedding machine; hence we also design and manufacture plastic shredder machine